Ambulantno zdravljenje venske tromboze - Azarija, Jelena (Zdravniški vestnik, 2009)
Background Authors present the preliminary results of ambulatory treatment of vein thrombosis (VT) at the University Medical Centre Ljubljana Department of Vascular Diseases. In Slovenia ambulatory treatment of VT in form of a daily hospital has been carried out since 2005. Patients and methods From October 2005 to December 2006 we retrospectively reviewed 395 consecutive patients, treated for VT of lower or upper limbs. Diagnosis of VT was confirmed by ultrasound imaging. The physician on duty decided whether the patient will be treated in hospital or as an outpatient, on the ground of his/her clinical condition and compliance in the treatment process. Results In the ambulatory treated group were 198 patients (108 men and 90 women), aged 58 (42.72) years.In the hospital treated group there were 197 patients (91 men and 106 women), aged 73 (57.80) years. Patients treated in the hospital were older than patients treated ambulatory, had more frequently associated pulmonary embolism (PE), malignancies and immobilization. In the latter group, the use of oral contraceptives and hormone replacement therapy was significantly more frequent. The time needed to achieve the therapeutic range of INR (2.0.3.0) was longer in the ambulatory treated group. More patients were admitted to theambulatory treatment during weekdays and more patients were admitted to thehospital on weekends and during holidays. More patients admitted to the ambulatory treatment were from Ljubljana and more patients admitted to the hospital were from more distant locations. In the ambulatory treated group none of the patients had complications during the acute phase of VT. Seven patients treated in hospital survived complications: two massive PE, five major bleeding. Eight patients treated in hospital died: four had PE, two septic shock, one heart failure and one terminal malignancy. (Abstract truncated at 2000 characters)
Keywords: Adipose Tissue; ambulantno zdravljenje; Atherosclerosis; cardiovascular disease; Cardiovascular Diseases; Debelost; Endotelij žilni; Endothelium, Vascular; Insulin Resistance; Insulinska rezistenca; Kardiovaskularne bolezni; Maščobno tkivo; Obesity; Pathology; Policistični jajčnik, sindrom; Polycystic Ovary Syndrome; Renin-Angiotensin System; Renin-angiotenzin, sistem; therapy; venska tromboza; zdravljenje